Plan exportador de café del os productores "LOS ANDES" hacia el mercado australiano (2021)
This project is born from the search of LOS ANDES coffee producers to export their product and manage to take it to a foreign market such as the Australian market, for this it is intended that this document serve as a tool capable of guiding entrepreneurs in their internationalization process in such a way that they can know all the processes, requirements and costs that are incurred when carrying out an export. Thus, research, data analysis and quotes were developed in order to be able to present accurate information capable of giving a clear vision of how the coffee market is in Australia, the internationalization routes and the financial analysis of the project for in this way provide clear conclusions and recommendations against the proposed objective